Toponimi Nama-Nama Tempat Wisata Di Kawasan Ekonomi Kreatif (KEK) Mandalika Kabupaten Lombok Tengah: Kajian Etnolinguistik - Fahimah Saifuddin; Lalu Dwi Satria Ardiansyah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The Mandalika Creative Economic Zone (KEK) is an area that is familiar to tourism lovers, especially marine tourism lovers. There are several beaches with white sand and beautiful waves that can attract visitors to visit this area. Almost all the beaches in this area are familiar to most people, such as Kuta beach, Bukit Merese beach, Aan beach, Batu Payung, Bukit Seger, Taman Mandalika beach. Those areas are very interesting to study, especially examining the origins and history of the naming of this tourist spot. Therefore, this research examines the toponymy of the names of tourist attractions in the Mandalika Creative Economy Zone (KEK), Central Lombok in terms of linguistic unit form and meaning. The aim of this research is (1) to describe the toponymy of the names of tourist attractions in the Mandalika Region of Central Lombok (2) to describe the history of the names of tourist attractions in the Mandalika Region of Central Lombok. This research was carried out in three stages, namely the stage of providing data, analyzing data, and presenting the results of data analysis. Primary data was obtained through interviews with key informants in the local area. Data is provided using two methods, namely the listening and speaking methods. The results obtained from this research were the toponymy of the names of tourist attractions in the Mandalika Creative Economic Zone (KEK), namely the toponymy category based on the embodiment aspect and the toponymy category based on the cultural aspect.